Engineering of a Cytidine 5′‐Monophosphate‐Sialic Acid Synthetase for Improved Tolerance to Functional Sialic Acids. Issue 18 (9th September 2013) - Yi, Dong; He, Ning; Kickstein, Michael; Metzner, Julia; Weiß, Martin; Berry, Alan; Fessner, Wolf‐Dieter
Abstract Sialic acid‐containing glycoconjugates at the cell surface are of high importance in carbohydrate‐mediated recognition phenomena in physiological and pathological events, as well as in bacterial or viral infection. A key step in the enzymatic synthesis of natural sialoconjugates and functional synthetic analogues is the activation of sialic acids to cytidine 5′‐monophosphate (CMP)‐sialic acid intermediates catalyzed by CMP‐sialic acid synthetase (CSS). Based on our recently developed aligned protein model of substrate binding and a simple colorimetric screening assay, we have engineered the CSS from Neisseria meningitidis by structure‐guided site‐specific saturation mutagenesis at positions 192/193 to generate enzymes with broadened substrate scope. Top hits, including the F192S/F193Y variant, display an improvement of up to 70‐fold catalytic efficiency relative to wild‐type CSS for the conversion of sterically demanding N‐acyl modified sialic acid analogues, without compromising protein stability. Such significantly enhanced substrate capacity is a major step forward to realizing a generalized chemo‐enzymatic strategy for the efficient preparation of neo‐sialoconjugate libraries, demonstrated by the highly efficient, regio‐ and stereospecific synthesis of 2, 6‐sialyllactose analogues by enzymatic coupling to the highly substrate tolerant α2, 6‐sialyltransferase from Photobacterium leiognathi JT‐SHIZ‐145. Our results further document the unusual versatility of the N. meningitidis CSS and engineered variants for a common synthetic approach to sialoconjugates comprising a large diversity of natural and non‐natural sialic acid forms without the need for post‐synthetic enzymatic modification. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>